ENHANCING LISTENING COMPREHENSION THROUGH YOUTUBE: EFFECTIVENESS AND LEARNER CHALLENGES - Soali, Muhammad (LPPM Universitas Harapan Bangsa, 2024)
YouTube is a popular platform for sharing educational videos, including those that assist language learners. This Classroom Action Research study was conducted at Universitas Harapan Bangsa, Central Java, to evaluate the effectiveness of YouTube videos in enhancing students' literal and inferential listening comprehension skills at Language Development Center program. The population for this study consists of first-semester students from the D4 Anesthesiology Nursing Program in the Faculty of Health. The research aimed to determine (1) the impact of YouTube on listening skills and (2) the challenges encountered in its implementation. Conducted over two cycles, the study utilized observations, journals, and questionnaires for data collection, analyzing both qualitative and quantitative results. Findings revealed that YouTube videos significantly improve students' listening skills, create a positive classroom atmosphere, and boost motivation for out-of-class practice, particularly through exposure to diverse English accents. Additionally, the integration of multimedia resources supports differentiated learning, catering to various student needs and learning styles. However, challenges such as unstable internet connections and students' preferences for familiar accents were identified. Overall, YouTube videos are effective tools for teaching listening skills and offer great potential for enhancing other aspects of language learning, warranting further exploration in educational research.Keywords: YouTube Videos, Listening Comprehension, Literal Listening Skills, Inferential Listening Skills.